Prediction by the maximum oxygen consumption in terms of the concentration of lactic acid after the maximum physical effort for football players (18-25 years) - Jawad, Mohammed; Jabbar Shinen, Ibrhim (Journal of Physical Education, 2016)
The objectives of research to identify the maximum consumption of oxygen index (VO2max) predictable by knowing the concentration of lactic acid after the maximum physical effort and determine the percentage contribution of the concentration of lactic acid in the maximum consumption of oxygen index (VO2max) and find the equations of predictive indicator under study suppose the researchers that there is a statistically significant correlation between reduction index Aqsa for the consumption of oxygen and the concentration of lactic acid after the maximum physical effort and physical effort maximum influence constant variable under study and the researchers used the descriptive style of one group were identified variables of the maximum consumption of oxygen and the concentration of acid Allaktk in the blood on a sample of soccer players totaling 60 player after collecting data for research it has been reached that the highest measure of lactic be in the first minute of hospitalization after the effort and gradually decreases and predictable by the maximum oxygen consumption by measuring lactic in the first, third, fifth and seventh minute.